"Basal cell carcinoma of the hand: A systematic review and meta-analysis of incidence of recurrence". (March 2023) - Mortada, Hatan; Aldihan, Rema; Alhindi, Nawaf; Abu alqam, Rakan; Alnaim, Muna Faisal; Kattan, Abdullah E.
Abstract: Background: Hand basal cell carcinoma is a rare and complex disorder. Due to the hand's anatomical features, managing hand BCC is challenging. Therefore, we have conducted this systematic review to investigate various clinical characteristics, investigations, and treatment options related to hand BCC. Furthermore, a meta-analysis was used to provide pooled recurrence rates. Methods: We conducted this review per the International Prospective Register of Systematic Reviews (PROSPERO) guidelines. This study performed a systematic literature review in February 2022 using the following electronic databases: Cochrane, MEDLINE, and EMBASE. Key terms include hand basal cell carcinoma, basal cell carcinoma, management, outcome, and recurrence. We evaluated articles according to predefined quality criteria. Results: The study included 9725 patients and 51 published articles. A total of 35 case reports, 2 case series, 1 prospective study, and the remaining retrospective studies were evaluated. An asymptomatic skin lesion was the main complaint. In 10 studies, Moh surgery was the most frequently used treatment method. In the seven studies included in the meta-analysis, the overall incidence rate of recurrence among the included patients was 1.49 cases per year. Conclusion: The optimal extent of surgical treatment is still controversial, though an early biopsy can help identify lesions at an early stage. It is the first study to provide occurrence rates based on a meta-analysis. Developing treatment guidelines for BCC of the hand will be the focus of future research.